Cuido muito os meus pés: saberes e práticas de pessoas com diabetes mellitus tipo 2 - Leal, Tifany Colomé (2017)
Currently, diabetes mellitus is one of the largest health emergencies in the world. Type 2 diabetes mellitus is present in 90 to 95% of cases. It is characterized by defects in insulin action and secretion. The increased incidence of the disease in developing countries occurred concurrently with its complications. One of the problems of diabetes, are the ulcerations in the lower limbs, also called diabetic foot. Foot ulcers present an annual incidence of 2% and affect 25% of individuals with diabetes in the course of their disease. Those that affect mainly the feet, are considered the most serious, not only by the fact of the amputations, but also, by the high morbidity, mortality and the generated expenses in the public health. Thus, Nursing as a profession assumes an important and essential role in the perspective of the prevention of diabetic foot in people with type 2 DM. To this end, it is necessary for nurses and other health professionals to be aware of the knowledge and practices that People in their process of becoming ill. In this way, the specific objectives of this research were: to know the knowledge and practices of people with type 2 diabetes mellitus about diabetic foot; And, identify the care practices of people with type 2 diabetes mellitus in outpatient follow-up. This is a qualitative, exploratory and descriptive field research, conducted through a narrative interview and simple observation at the home of eight people with diabetes, who were accessed and invited to participate in the survey in the outpatient service of a public hospital in the Rio Grande do Sul. The data were worked by Minayo's operational proposal. The research followed the ethical principles of Resolution number 466/12 and obtained approval from the Committee of Ethics in Research with Opinion of number 1,499,174, number of CAAE 53936516.3.0000.5346. The results are presented in scientific paper format - Article 1: "Diabetic Foot: Knowledge and Practices of People with Type 2 Diabetes Mellitus" and Article 2: "Learning to Deal with the Enemy: Diabetes Mellitus Type 2 Care Practices". It was possible to identify that people have inconsistent information regarding the knowledge about diabetic foot. However, it was noticed that even though they did not know what the diabetic foot was, the participants performed care consistent with that recommended by specialists in the area. It is clear in the narrative of the interviewees the concern to preserve the lower limbs of injuries, to make use of comfortable shoes, to hydrate the foot in order to avoid cracks, to carry out hygiene in the interdigital spaces, among other care. About diabetes mellitus, people with diabetes have discovered in different ways their diagnosis, know the complications of the disease and perform care practices related mainly to food. It is important to emphasize the need to approach popular and scientific knowledge in order to establish effective care.